Memahami Dan Meneladani Penderitaan-Kematian Kristus: Seri Pembinaan Iman Di GKII Shalom, Yogyakarta - Lie Agan; Jessi Darius (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2023)
The background to this Community Service activity is: First, there is a need to refresh the understanding of 'Being like Christ', especially in terms of the characteristics of facing suffering, in the context of the weeks leading up to the commemoration of Good Friday. Second, there is a tendency for believers to doubt the perfection of Christ's sacrifice for salvation, with contemporary teachings, especially progressive Christianity which emphasizes good deeds in salvation, not the work of Christ. The purpose of this article is: First, to explain the meaning of 'becoming like Christ' for believers. Second, to explain the perfection of Christ's sacrifice for human salvation. The method used to present this article is the descriptive method, while the method used in the activity is the lecture method. The results of this activity are: First, becoming like Christ according to Philippians 2:6-8 in terms of humility (verses 6-7), obedience to God (8a) and willingness to sacrifice (8b). The perfection of Christ's sacrifice according to Hebrews 10:1-5 shows that Christ's sacrifice is superior to the sacrifices in the Old Testament (1-7), Christ's sacrifice was carried out once and for all (10), Christ's sacrifice perfected the salvation of believers (14). Second, the results of audience satisfaction are as follows: Data on the average level of satisfaction from the two activities, namely from 50 samples who gave answers to the satisfaction level questionnaire: no people (0%) said they were dissatisfied, 1 person (2.0%) said less satisfied, 3.5 people (6.94%) said they were neutral, 40 people (79.09%) said they were satisfied and 6 people (12.00%) said they were very satisfied. It can be concluded that the majority of respondents expressed satisfaction, and a small percentage stated they were very satisfied. The level of respondent satisfaction is high.